Establishing a stem cell culture laboratory for clinical trials - Elíseo Joji Sekiya; Andresa Forte; Telma Ingrid Borges de Bellis Kühn; Felipe Janz; Sérgio Paulo Bydlowski; Adelson Alves (Revista Brasileira de Hematologia e Hemoterapia, 2012)
Adult stem/progenitor cells are found in different human tissues. An in vitro cell culture is needed for their isolation or for their expansion when they are not available in a sufficient quantity to regenerate damaged organs and tissues. The level of complexity of these new technologies requires adequate facilities, qualified personnel with experience in cell culture techniques, assessment of quality and clear protocols for cell production. The rules for the implementation of cell therapy centers involve national and international standards of good manufacturing practices. However, such standards are not uniform, reflecting the diversity of technical and scientific development. Here standards from the United States, the European Union and Brazil are analyzed. Moreover, practical solutions encountered for the implementation of a cell therapy center appropriate for the preparation and supply of cultured cells for clinical studies are described. Development stages involved the planning and preparation of the project, the construction of the facility, standardization of laboratory procedures and development of systems to prevent cross contamination. Combining the theoretical knowledge of research centers involved in the study of cells with the practical experience of blood therapy services that manage structures for cell transplantation is presented as the best potential for synergy to meet the demands to implement cell therapy centers.